Clinical efficacy of conservative laser therapy for early-stage cervical cancer. Issue 2 (1st February 2007) - Yamaguchi, H.; Ueda, M.; Kanemura, M.; Izuma, S.; Nishiyama, K.; Tanaka, Y.; Noda, S.
Abstract : The objective of this study was to evaluate the clinical efficacy of conservative laser therapy for early-stage cervical cancer. Seven hundred fifty-two and 271 patients with carcinoma in situ (CIS) and microinvasive squamous cell carcinoma (MIC), respectively, were treated by laser conization with vaporization. One hundred eighty-four patients with preclinical invasive diseases underwent radical surgery without conization. Their postoperative histologic findings and clinical outcomes were evaluated retrospectively. The cone specimens of 1023 cases were reported as showing that 54 had dysplasia, 663 had CIS, 239 had stage Ia1 without lymph vascular space invasion (LVSI), 14 had stage Ia1 with LVSI, 14 had stage Ia2, and 39 had stage Ib1 diseases. Incomplete excision occurred in 4 (7.4%) of 54 dysplasia, 48 (7.2%) of 663 CIS, and 16 (6.7%) of 239 stage Ia1 cases, but failure rates were only 1 (1.9%), 8 (1.2%), and 4 (1.7%), respectively. The other 67 of 1023 cases underwent abdominal operation. Final pathology results were analyzed for 67 and 184 cases with stages Ia1 to Ib1 receiving radical surgery with or without initial laser therapy. Lymph node metastasis was not observed in 154 Ia1 and 30 Ia2 with stromal invasion of under 4 mm in depth regardless of LVSI, but was detected in 2 of 16 Ia2 with stromal invasion of over 4 mm in depth and in 9 of 51 Ib1 cases. CIS and Ia1 disease without LVSI can be treated only by laser therapy. The limit of stromal invasion for conservative laser therapy in stage Ia cancer may be 4 mm in depth regardless of LVSI.